Sold down the river : slavery in the lower Chattahoochee Valley of Alabama and Georgia - Carey, Anthony Gene (University of Alabama Press, 2011)
In the New World, the buying and selling of slaves and of the commodities that they produced generated immense wealth, which reshaped existing societies and helped build new ones. From small beginnings, slavery in North America expanded until it furnished the foundation for two extraordinarily rich and powerful slave societies, the United States of America and then the Confederate States of America. The expansion and concentration of slavery into what became the Confederacy in 1861 was arguably the most momentous development after nationhood itself in the early history of the American republic. This book examines a relatively small part of slavery's North American domain, the lower Chattahoochee river Valley between Alabama and Georgia. Although geographically at the heart of Dixie, the valley was among the youngest parts of the Old South; only thirty-seven years separate the founding of Columbus, Georgia, and the collapse of the Confederacy. In those years, the area was overrun by a slave society characterized by astonishing demographic, territorial, and economic expansion. Valley counties of Georgia and Alabama became places where everything had its price, and where property rights in enslaved persons formed the basis of economic activity. Sold Down the River examines a microcosm of slavery as it was experienced in an archetypical southern locale through its effect on individual people, as much as can be determined from primary sources.